Islamic Da‘wah and its Methodology in the Contemporary Times: A Study of Tablīghī Jamā‘at - Nazir Ahmad Zargar (Penerbit Hellow Pustaka, 2026)
This paper explores the methodology and practices of Islamic Da‘wah in contemporary times, with a particular focus on the Tablīghī Jamā‘at. Da‘wah, the act of inviting others to Islam, is a fundamental aspect of the faith, and its methods have evolved over time to adapt to changing societal contexts. The Tablīghī Jamā‘at, a global Islamic missionary movement, has gained prominence for its grassroots approach to spreading the message of Islam. This study examines the historical roots of the Tablīghī Jamā‘at, its organizational structure, and its strategies for engaging with diverse communities. By analyzing the Tablīghī Jamā‘at's methodologies, this paper aims to provide insights into the broader landscape of Islamic Da‘wah in the contemporary world. Through an exploration of its principles, activities, and impact, this research contributes to a deeper understanding of the role of Islamic missionary movements in shaping Muslim communities and promoting religious outreach in the modern era.